1997
DOI: 10.1177/174182679700400102
|View full text |Cite
|
Sign up to set email alerts
|

Women Married to Men with Myocardial Infarction are at Increased Risk of Coronary Heart Disease

Abstract: Aim To measure the prevalence of coronary heart disease (CHD) risk factors in the female partners of men with acute myocardial infarction (AMI).Method Consecutive incident cases of men under 6 5 years of age with AM1 surviving to 3 months, their female partners and female healthy controls matched for age and marital status drawn from the general population were investigated. ResultsOne-hundred and seventeen cases of AM1 in men under 6 5 years of age and 89 female partners were identified; 133 age-and sex-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It is truly multidisciplinary with participants meeting multiple, specially trained healthcare professionals who participate in joint decision-making at weekly meetings. The family-orientated approach is adopted since families tend to share risk factors 45 and people are more likely to succeed in behavioural change if the entire family are embracing lifestyle modification. 46 The programme is flexible, offering a range of attendance options tailored to the patient’s individual needs, and we suspect that this type of approach most likely contributed to the high retention rates observed on the programme.…”
Section: Discussionmentioning
confidence: 99%
“…It is truly multidisciplinary with participants meeting multiple, specially trained healthcare professionals who participate in joint decision-making at weekly meetings. The family-orientated approach is adopted since families tend to share risk factors 45 and people are more likely to succeed in behavioural change if the entire family are embracing lifestyle modification. 46 The programme is flexible, offering a range of attendance options tailored to the patient’s individual needs, and we suspect that this type of approach most likely contributed to the high retention rates observed on the programme.…”
Section: Discussionmentioning
confidence: 99%
“…1,7 Interestingly, the benefits of cardiac rehabilitation may include partners of patients with CHD as cardiac risk factors are often shared. 8,9 Therefore, promotion of physical activity in the family members of patients with CHD attending cardiac rehabilitation is also worthwhile.…”
Section: Introductionmentioning
confidence: 99%
“…However, although extensive research has been carried out investigating risk factors, especially smoking habits, blood pressure and blood lipid levels, for developing CAD in first-degree relatives of patients with CAD, who have a strong genetic predisposition, there is a lack of research investigating risk factors in the wives of this particular group of patients, who would possibly have a similar environmental influence. In particular, there have been only a limited number of studies investigating CAD risk factors in wives of patients with myocardial infarction (MI) which have shown that this particular group is in a higher risk than wives of normal healthy controls [10][11][12]. However, these studies were carried out in Norway, USA and the UK, where lifestyle is different from that in Greece.…”
Section: Introductionmentioning
confidence: 99%